2016
DOI: 10.1016/j.ijrmhm.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Densification of W–Ni–Fe powders using laser sintering

Abstract: In this paper, Laser Sintering (LS) of 90%W-7%Ni-3%Fe (wt.%) powders have been investigated, with the goal to understand the influence of final density by laser power, scanning speed, laser trace width, and the number of scanning passes. The results suggest that the laser power and scanning speed are the most important factors influencing density; the influence of trace width and number of scanning passes are not significant. With the in crease of laser power and decrease of scanning speed, higher density can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In this process, the component which has lower melting temperature fuses and makes an adjoin between metal powders [19,20]. It is strongly emphasized that the accuracy of a part depends on careful selection of process parameters and unsuitable selection of process parameters will lead to part distortion, balling phenomena and dross formation [1,3,18,21,22]. The effective parameters of laser sintering can be divided into three general categories: process parameters, material parameters and environmental parameters [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the component which has lower melting temperature fuses and makes an adjoin between metal powders [19,20]. It is strongly emphasized that the accuracy of a part depends on careful selection of process parameters and unsuitable selection of process parameters will lead to part distortion, balling phenomena and dross formation [1,3,18,21,22]. The effective parameters of laser sintering can be divided into three general categories: process parameters, material parameters and environmental parameters [23].…”
Section: Introductionmentioning
confidence: 99%
“…Also increasing in the number of manufactured layers causes increasing temperature if no preheating is in use [18]. Wang et al reported that the laser scanning speed and laser power are the most effective parameters on density of fabricated parts [22]. They also derived a densification model to predict density.…”
Section: Introductionmentioning
confidence: 99%
“…The density is a very important quality of the finished part because it has a direct relationship to strength, weight, and integrity. Wang et al (2016) have proposed a model to predict the relative density based on the processing parameters used within the scan. They were able to conclude that the most important parameters were the scanning speed and laser powder.…”
Section: Layer Additionmentioning
confidence: 99%
“…Advanced functionality and complex model considerations are then described and incorporated into the final model. Next, numerous simulations were conducted using W-Ni-Fe as the powder material and the results were compared to an experiment performed by Wang et al (2016). Additionally, a second study was performed in which 316L stainless steel was as the material.…”
Section: General Approachmentioning
confidence: 99%
See 1 more Smart Citation